Rock Support Design for the Khimti I Hydropower Project - Sunuwar, S. C.; Shrestha, G. L.; Neill, B. O' (Journal of Nepal Geological Society, 2000)
The Khimti I Hydropower Project (KHP) is the first project where the Norwegian Method of Tunnelling (NMT) was applied in Nepal. The method was found to be appropriate for drill-and-blast tunnels in jointed, fractured, and sheared rocks, which tend to overbreak. A combination of rock bolting with wet fiber reinforced shotcrete is the main rock support method in the NMT. In exceptionally poor rock (with squeezing conditions) reinforced ribs of shotcrete with a concrete invert were generally found to be a more efficient and cost effective. Cast concrete lining was also used occasionally at the KHP, mainly in overbreak areas with high groundwater discharge. The main advantage of the NMT is that each stretch of tunnel is evaluated using the Q-System of rock classification and then only the required amount of support is applied. This procedure takes optimum advantage of the self-supporting capacity of the rock. There were some problems encountered during application of the NMT at the KHP, but the adoption of 10 site -specific design principles made the method more practical and effective. It was generally experienced that the NMT was simple to use and gave appropriate guidelines that could be applied across a very broad range of rock conditions. At Khimti, the peak excavation rates reached 63 m/week and 72 m/week in 25 m2 and 14 m2 tunnels, respectively. The average excavation rates (including full support) were 10 m and 35 m per week in "Extremely Poor" and "Poor to Fair" rock conditions, respectively.